Internal point of view and importance of concept of the communicational community in methodology of jurisprudence (introduction to the issues) - Marek Zirk-Sadowski; Tomasz Bekrycht (Acta Universitatis Lodziensis Folia Iuridica, 2017)
The text contains some remarks on the methodological issues of jurisprudence. It points to important role of the so-called internal point of view in epistemology of law and it stresses an important role of the analysis of legislative language (language of the law) and legal language in an attitude of the participant of the communicational community.